Karakteristik Morfologi Benih sebagai Parameter untuk Penentuan Pohon Induk Sumber Benih Pala (Myristica fragrans Houtt.) - Pramudita, Listya; Widajati, Eny; Suwarno, Faiza Chairani; Surahman, dan Memen (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Nutmeg is an Indonesian native plant, produces essential oill as an export commodity. However, it has low seed uniformity that mengurangi keseragaman tanaman di lapang. The main objective of this research was to obtain morphological characteritics as parameter for nutmeg mother plants selection. This field research was carried out from August-December 2014 at Toisapu, Wakal and Lula nutmeg seed source plantations in Ambon, and Seed Storage and Testing Laboratory, IPB. Characterization was undertaken on ten mother plants from each Wakal and Lula seed source plantations and eight mother plants from Toisapu seed source plantation. Quantitative and qualitative characters of vegetative, fruit, mace and seed from every mother plants were analyzed with Gower’s similarity test. Mother plants that produced high uniformity seed was the 7th (0.80), the 8th (0.93) and the 10th (0.80) mother plants in Wakal; the 2nd (0.80) mother plant in Toisapu; the 2nd (0.82), the 5th (0.80), the 6th (0.82), the 8th (0.84), the 9th (0.80) and the 10th (0.93) mother plants in Lula. Those selected mother plants produced morphological uniform seed morphologically. Lula seed plantation had the highest uniformity level among mother plants (0.77-0.87) compared to Toisapu (0.70-0.87) and Wakal (0.69-0.84) mother plants. The morphological characteristic can be use to select the source seed mother plants which able to produce high morphological uniformity seeds.Keywords: Gower’s similarity, seed production, uniformity